Socialization of The Using of Disinfectants In Cattle as an Effort To Prevent The Transmission of Foot And Mouth Diseases (FMD) In Sumber Rejeki, Dau, Malang - Habib Syaiful Arif Tuska; Vanessa Prudence Orlona; Indah Amalia Amri; Fidi Nur Aini; Gretania Residiwati (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
Foot and Mouth Disease (FMD) is a contagious animal disease that attacks livestock. The Sumber Rejeki Dairy Cattle Group in Gading Kulon Village, Malang Regency has 356 cows of the Friesian Holstein breed. Several cows in Sumber Rejeki has been infected with the PMK virus. This disease causes a decrease in milk production in infected cows, causing economic losses to KSP breeders. Source of fortune. One of the efforts to prevent its spread is to disinfect the cage. Disinfection of cages is effective enough to kill the FMD virus because the FMD virus does not have an outer membrane and is easily destroyed at pH <5 and >7. Community knowledge regarding disinfection is still low, so socialization is carried out regarding the provision of disinfectants in cages. After the socialization, there was an increase in the knowledge of the farmers by 41.5% through the pretest and posttest which were given before and after the socialization.